Novel Double-Terminal Traveling Wave Fault Location Method for Railway Power Transmission Lines - Kaiqing Tian; Yuhang Fan; Wenyan Feng (IEEE Access)
Traveling wave (TW) fault location holds great promise for railway power transmission lines. However, the single-terminal method struggles with identifying the second wavefront and has issues with wave velocity accuracy. The double-terminal method necessitates strict clock synchronization. This paper introduces a novel double-terminal TW fault location method that merges the benefits of both approaches. By examining the fault TW propagation characteristics and paths in railway power transmission lines, this method leverages the time gap of initial voltage Traveling waves between ground-mode and aerial-mode at both ends of the substation. This approach, through formula derivation, eliminates the influence of wave velocity and removes the need for data synchronization between the terminals. Simulations using a railway power transmission line model in PSCAD/EMTDC demonstrate that this method not only retains the advantages of traditional TW fault location methods but also avoids the need to identify the second wavefront, is unaffected by wave velocity, and does not require double-terminal clock synchronization. Simulation results show that the method achieves high accuracy, with fault location errors within 400 m.